Probable First Sighting of Dark Morph of Eastern Cattle-EGRET Bubulcus coromandus from Lakhimpur Kheri, Uttar Pradesh, India - Singh, Satpal (Journal of the Bombay Natural History Society (JBNHS), 2012)
No Abstract.